The small subunit of the vaccinia virus early transcription factor contacts the transcription promoter DNA. - Broyles, S S (1993)
The vaccinia virus early transcription factor (VETF), in addition to the viral RNA polymerase, is required for efficient transcription of early genes in vitro. VETF is a heterodimeric protein that binds specifically to early gene promoters. In order to localize the VETF DNA binding domain, we have used photoreactive oligonucleotide probes with the sequence of the vaccinia virus growth factor promoter. The probes consisted of double-stranded oligonucleotides incorporating radiolabeled dAMP and 5-bromo-dUMP into sequences of the promoter known to contact VETF. Irradiation of a DNA probe having these nucleotides located upstream of the transcription start site in the presence of VETF resulted in the transfer of label to a polypeptide that comigrated with the small subunit of VETF. The label transfer reaction was shown to occur with the recombinant VETF small subunit in the absence of the large subunit. These results indicate that the small subunit comprises at least part of the VETF DNA binding domain and contacts the promoter in the region upstream of the transcription start site.